Flux Creep Investigation in Bi2Sr2CaCu2O8+d High-Temperature Superconductor - Blanca, G. R.; Ronulo, J.; Dumlao, G.; Sarmago, R. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 16 No 2 (2004), 2007)
The flux creep process in a c-axis Bi2Sr2CaCu2O8+d thin film was investigated at different temperatures and applied fields using the Kim-Anderson (KA) approach. The peaked behavior shown in the magnetoresistance profile was attributed to the competing mechanisms of flux motion and sample-intrinsic transition near Tc.Within the temperature range where the competition occurs, U increases with temperature and consequently a decrease in the superconducting volume corresponds to a decrease in the flux creep. Moreover, the flux creep potential barrier varies with applied current I at all temperatures consistent with the KA model.